2015
DOI: 10.1115/1.4030869
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Analysis of a Passenger Car at Yaw Angle and Two-Vehicle Platoon

Abstract: Experimental and computational studies were performed to study the drag forces and the pressure distributions of a one-fifth scale model FIAT Linea at increasing yaw angle and two-vehicle platoon. Experiments were performed in the Uludag University Wind Tunnel (UURT) only for the yaw angles of 0 deg, 5 deg, and 10 deg due to the test section dimensional restriction. Supplementary tests were performed in the Ankara Wind Tunnel (ART) to evaluate the aerodynamic coefficients up to yaw angle of 40 deg. The test se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…where the subscripts 1 and 2 in equation (17) represent the values of a coefficient f in the inner or k À v and outer or k À regions, respectively, and F 1 is a weighting function as defined in equation (20). For example, if we consider the s k coefficient in the k-transport equation (equation (13)), equation (17) reads as…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the subscripts 1 and 2 in equation (17) represent the values of a coefficient f in the inner or k À v and outer or k À regions, respectively, and F 1 is a weighting function as defined in equation (20). For example, if we consider the s k coefficient in the k-transport equation (equation (13)), equation (17) reads as…”
Section: Methodsmentioning
confidence: 99%
“…Existing literature shows studies covering yaw and pitch effects on generalized car shapes, such as the Ahmed et al 2 body and passenger cars, both experimentally [3][4][5][6][7] and computationally. [8][9][10][11][12][13] However, similar efforts with a direct motorsports application are almost non-existent, be it numerical or experimental. The short literature list in this area includes a recent computational work on the rear wing end-plate investigation conducted by Gogel and Sakurai 14 and a pitch sensitivity examination on a generic F1 car by Zhang et al 15 Both these studies focused on the open-wheel type racecar configurations, and were conducted using the steady-state Reynolds Averaged Navier-Stokes (RANS) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…More recent numerical campaigns include Large Eddy Simulations (LES) by Uystepruyst and Krajnović (2013), who observed drag reductions in keeping with Tsuei and Savaş (2001) for a four-cuboid platoon at relatively small inter-vehicle spacing. On two-vehicle platoons, considerable drag benefit was identified by Altinisik et al (2015), based on the numerical and experimental study on a twocar platoon with various inter-vehicle spacings, for the lead car, especially with smaller intervehicle spacing, but no drag reduction was observed for the trailing car. LES of a similar type vehicle travelling in a two-vehicle platoon was also conducted by Mirzaei and Krajnović (2016) who again noted the drag penalty the when inter-vehicle spacing was equal to half of the vehicle length.…”
Section: Introductionmentioning
confidence: 99%
“…Square-back vehicles were likely found to give more drag reduction than vehicles with a more tapered back. Altinisik et al 4 conducted experiments for platoons with yaw angle and maximum drag coefficient was obtained at yaw angle of 35°. Humphreys and Bevly 5 found that fuel economy for trucks in platoon improves as the separation distance diminishes.…”
Section: Introductionmentioning
confidence: 99%